PENGARUH eWOM DAN e-REFERRAL TERHADAP NIAT PEMBELIAN: PERAN CITRA MEREK SEBAGAI VARIABEL MODERASI - Ridwan Abdul Aziz; Herlina Lusmeida (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This research was conducted to provide empirical evidence on the effect of the quality of Sustainable Development Goals (SDGs) disclosure and green accounting on financial performance. This study uses SDGs disclosure and environmental costs as independent variables, and Return on Assets and Return on Equity as dependent variables. The study employs secondary data from the sustainability reports of 180 non-financial companies from 2020 to 2024. This quantitative research is based on a positive paradigm, with samples selected using purposive sampling and analyzed using multiple linear regression with SPSS version 29. The results of this study indicate that (1) the quality of SDGs disclosure has no effect on financial performance, and (2) green accounting has no effect on financial performance. The implication of this research is that the quality of SDGs disclosure does not influence the financial performance of companies